Inhibition of Progenitor Dendritic Cell Maturation by Plasma from Patients with Peripartum Cardiomyopathy: Role in Pregnancy-associated Heart Disease - Jane E. Ellis; Aftab A. Ansari; James D. Fett; Robert D. Carraway; Hugh W. Randall; Mario I. Mosunjac; J. Bruce Sundstrom (Clinical and Developmental Immunology)
Dendritic cells (DCs) play dual roles in innate and adaptive immunity based on their functional maturity, and both innate and adaptive immune responses have been implicated in myocardial tissue remodeling associated with cardiomyopathies. Peripartum cardiomyopathy (PPCM) is a rare disorder which affects women within one month antepartum to five months postpartum. A high occurrence of PPCM in central Haiti (1 in 300 live births) provided the unique opportunity to study the relationship of immune activation and DC maturation to the etiology of this disorder. Plasma samples from two groups (n = 12) of age- and parity-matched Haitian women with or without evidence of PPCM were tested for levels of biomarkers of cardiac tissue remodeling and immune activation. Significantly elevated levels of GM-CSF, endothelin-1, proBNP and CRP and decreased levels of TGF- were measured in PPCM subjects relative to controls. Yet despite these findings, in vitro maturation of normal human cord blood derived progenitor dendritic cells (CBDCs) was significantly reduced (p < 0.001) in the presence of plasma from PPCM patients relative to plasma from post-partum control subjects as determined by expression of CD80, CD86, CD83, CCR7, MHC class II and the ability of these matured CBDCs to induce allo-responses in PBMCs. These results represent the first findings linking inhibition of DC maturation to the dysregulation of normal physiologic cardiac tissue remodeling during pregnancy and the pathogenesis of PPCM.